MULTI-DOMAIN SELECTION OF APTAMERS FOR BACTERIAL PROTEINS: TARGETING FUSOBACTERIUM NUCLEATUM DNAK - Rey Rincon, Maria Alejandra (My University, 2020)
Aptamers are nucleic acid ligands that bind to a specific target molecule. They are discovered by in-vitro selection, whereby binding sequences are selected from a large library of random sequences through iterative affinity steps. Aptamers are used as molecular recognition elements in aptamer-based, as such, creating aptamers with high affinity and specificity to their targets is important to the field. Ligands with two binding sites have been reported to have enhanced binding affinity than ligands with one binding site. To improve the quality of aptamers for downstream applications, multidomain selection is proposed as a new method for selecting aptamers compatible with dimerization. Here, we applied the multidomain selection approach to Fusobacterium nucleatum DnaK and produced aptamers that target the N-terminal domain (NTD) and the C-terminal domain (CTD) of DnaK. The top aptamer for DnaK-NTD had a Kd of 59.7 nM, and for DnaK-CTD had a Kd of 202.0 nM. However, the aptamers did not bind to the full-length DnaK and could not be dimerized. Multiple-site binding offers greater flexibility in the design of detection systems, which could provide higher selectivity and sensitivity than aptamers found through standard approaches. Validation of a method to discover aptamers compatible with dimerization would result in the development of a targeted approach to discover high-quality aptamers for bacterial proteins that can be used in bacteria-detection techniques.
Keywords: Aptamer; Selection; Fusobacterium nucleatum; DnaK; Functional DNA; Sensor; Colorectal Cancer